Detection and identification of Huo–Xue–Hua–Yu decoction (HXHYD) using surface-enhanced Raman scattering (SERS) spectroscopy and multivariate analysis. (25th February 2015) - Chen, Weiwei; Lin, Jia; Chen, Rong; Feng, Shangyuan; Yu, Yun; Lin, Duo; Huang, Meizhen; Shi, Hong; Huang, Hao
Abstract: We have evaluated the capabilities of surface-enhanced Raman scattering (SERS) technology for analyzing two Huo–Xue–Hua–Yu decoctions (HXHYDs) prepared according to different prescriptions. The aim of this study was to evaluate the relevance of SERS technology applied to decoction of traditional Chinese medicines (TCM). HXHYD I was prepared according to the original prescription; the same preparation method was used for the HXHYD II, except for the crudeweight ratio described in the original prescription. There was no Raman signal in conventional Raman spectra of HXHYDs. Silver nanoparticles were directly mixed with HXHYDs to enhance the Raman scattering of biochemical constituents, and high quality SERS spectra were obtained. Significant differences in SERS spectra between HXHYD I and II can be observed, which showed special changes in the percentage of biochemical constituents in different decoctions. Principal components analysis (PCA) combined with linear discriminant analysis (LDA) were employed to generate diagnostic algorithms for classification of SERS spectra of two HXHYDs, and showed that a diagnostic accuracy of 100% can be achieved. This work demonstrated that the SERS technique has potential for spectral characteristic detection for decoction of TCM with high sensitivity, and that this technique, combined with PCA-LDA, can be used for quality control of the extracted decoction of TCM and production management of Chinese herbal preparations.